Electrochemical polymerization of aniline in presence of TiO2 nanoparticles - Irena Mickova; Abdurauf Prusi; Toma Grčev; Ljubomir Arsov (Macedonian Journal of Chemistry and Chemical Engineering, 2006)
The electrochemical polymerization of aniline from acid aqueous solutions of 1 M H2SO4 in presence of TiO2 nanoparticles was performed by cyclic voltammetry. The heterogeneous polymerization of new synthesized materials from aniline monomers and electrodeposited TiO2 polymer coated nanoparticles was analyzed using electrochemical techniques. During the repetitive cyclic voltammetry scans the presence of TiO2 nanoparticles inhibits the polymer – related oxidation process and diminishes the degradation products in the composite materials. Good adhesion of composite materials on the Pt electrode, with superior electro-active repetitive properties in relation with pure polyaniline, was demonstrated.